2020
DOI: 10.1021/acs.bioconjchem.0c00355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycosylation and d-Amino Acid Substitution on the Antitumor and Antibacterial Activities of Bee Venom Peptide HYL

Abstract: Glycosylation is a promising strategy for modulating the physicochemical properties of peptides. However, the influence of glycosylation on the biological activities of peptides remains unknown. Here, we chose the bee venom peptide HYL as a model peptide and 12 different monosaccharides as model sugars to study the effects of glycosylation site, number, and monosaccharide structure on the biochemical properties, activities, and cellular selectivities of HYL derivatives. Some analogues of HYL showed improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Previous reports have shown that ACPs usually lost their activity due to enzymatic instability, which is one primary obstacle for ACP to be developed as anticancer drugs. ,, To increase the peptide stability, many effective strategies have been used in the ACP designs, such as the incorporation of unusual amino acids, backbone cyclization, , and modification of polymer. , In this study, our results suggested that the coupling of anionic peptide LE to LK via a disulfide linker could bestow a new peptide with high enzymatic stability to resist proteolysis compared to LK. The increase in α-helix generally stabilizes the structure of the peptide and enhances resistance to enzyme degradation .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous reports have shown that ACPs usually lost their activity due to enzymatic instability, which is one primary obstacle for ACP to be developed as anticancer drugs. ,, To increase the peptide stability, many effective strategies have been used in the ACP designs, such as the incorporation of unusual amino acids, backbone cyclization, , and modification of polymer. , In this study, our results suggested that the coupling of anionic peptide LE to LK via a disulfide linker could bestow a new peptide with high enzymatic stability to resist proteolysis compared to LK. The increase in α-helix generally stabilizes the structure of the peptide and enhances resistance to enzyme degradation .…”
Section: Discussionmentioning
confidence: 68%
“…Anticancer peptides (ACPs) have been introduced as alternative candidates to treat cancer with a certain degree of cancer cell selectivity, low tendency to drug resistance, good biocompatibility, and ease of synthesizing and modifying. Generally, they are relatively small peptides with variable cationic and amphipathic characteristics. They exhibit broad-spectrum antitumor activity through multiple action mechanisms. One prominent merit of ACPs is that these peptides could selectively disrupt the tumor cell membrane in a receptor-independent manner, which is different from that of conventional antineoplastic agents. , Despite this, the drawbacks of anticancer peptides, such as the toxicity at high concentrations and fast degradation in vivo, are still the main concerns for drug development. , To circumvent these limitations, many different strategies have been used to improve the therapeutic efficiency of ACPs, including amino acid substitution, fatty acid modification, , glycosylation, , backbone conjugation or cyclization, , and utilization of functionalized carriers. , Histidine modification is a simple and effective approach to develop smart pH-responsive ACPs with better selectivity for cancer therapy based on the tumor acidic environment, as histidine could protonate into a positive charge under the acidic tumor microenvironment from predominantly no charge in tissues with normal physiological conditions, thereby endowing peptides with a pH-activated charge conversion feature. , Hence, this type of histidine-based ACPs is inactivated under physiological conditions, while their antitumor activity can be activated in an acidified tumor microenvironment. Notably, the combination of unique histidine with negatively charged glutamate (Glu) is also a promising approach to obtaining acid-responsive recombinant peptides. , The cationic charge of these peptides can be first shielded by anionic glutamate under normal physiological conditions to alleviate their indiscriminative effect.…”
Section: Introductionmentioning
confidence: 99%
“…A study indicated that the glycosylation of a serine residue, such as that in stapled compounds 62 and 63 (see Table 2), further improved the proteolytic stability and selectivity. 63 In a different approach, instead of using a common S 5 residue, new amino acid derivatives were utilized in which both an αpentenyl moiety and a native side chain were present in the structure to replace the two positions L3 and K7, respectively, in the sequence of 64 (also called Anoplin) to generate 66 (see Table 2). 42 This strategy reintroduced the positively charged side chain of lysine, thus significantly increasing the hydrophilicity of 66 compared to that of the regular stapled version 65.…”
Section: Stapled Antimicrobial Peptides Asmentioning
confidence: 99%
“…Furthermore, the increased cytotoxicity of the peptides toward human red blood cells and other types of normal cells was still a major disadvantage. , , To solve this problem, some additional modifications were performed to increase the hydrophilic content of the peptide structure. A study indicated that the glycosylation of a serine residue, such as that in stapled compounds 62 and 63 (see Table ), further improved the proteolytic stability and selectivity . In a different approach, instead of using a common S 5 residue, new amino acid derivatives were utilized in which both an α-pentenyl moiety and a native side chain were present in the structure to replace the two positions L3 and K7, respectively, in the sequence of 64 (also called Anoplin ) to generate 66 (see Table ).…”
Section: Stapled Antimicrobial Peptides As Anticancer Agentsmentioning
confidence: 99%
“…However, more investigations are still necessary to explain the role of glycosylation in arthropod venoms. The manipulation of glycosylation in toxins analogues with potential therapeutic applications is also an alternative strategy to improve proteolytic stability, peptide/toxin activity and selectivity toward tumor cells [91].…”
Section: Glycosylation In Arthropod Venom Proteinsmentioning
confidence: 99%